The Household Consumption Decision of Staple Food Purchase in the Midst the Covid-19 Pandemic - Ahmad Zainuddin; Rudi Wibowo; Luh Putu Suciati; Intan Kartika Setyawati; Illia Seldon Magfiroh; Indah Ibanah; Rena Yunita Rahman; Evita Soliha Hani (SOCA: Jurnal Sosial Ekonomi Pertanian, 2022)
Covid-19 has brought surprising changes in the household behavior pattern and decision-making process in consuming food. Therefore, this study aimed to (1) identify household consumption pattern and purchase behavior due to the dynamics of supply shock during the Covid-19 pandemic and (2) analyze factors that influence household consumption decisions on food purchase during the Covid-19 pandemic. One hundred participants from Kaliwates and Sumbersari District, Jember Regency, had recruited by the cluster sampling technique. These districts were purposively selected as the study locations. Data were analyzed using logit analysis. Findings reported that variable of price, income, age, and residence dummy had significantly influenced the household consumption decision on food purchase during the pandemic at the level of=20%. Secure staple food stock is required, recalling the evidence that no significant change in the food consumption patterns documented in this study